Water challenges and Urban Sustainable Development in Changing Climate: Economic Growth Agenda for Global South - Raza, Tabassam; C. Rentoy, Frederika; Ahmed, Nisar; Thess Khas S. Raza, Andrea Valentine L. Andres; E. Marasigan, Karl Michael; M. Espinosa, Ramon Iñigo (European Journal of Sustainable Development, 2019)
Access to safe clean water and sanitation were pressing concerns for survivors after super Typhoon Haiyan devastated central Philippines in November 2013. Essentially, water problems in the cities of Global South especially in Southeast Asian Archipelagos (Philippines, Indonesia, and Malaysia) plus Myanmar and Thailand are viewed as the consequence of uncontrolled rapid urban development and Climate Change (CC) variations. These facts emphasized the link between water insecurity and its negative economic impact. Thus, an equal and inclusive agenda is developed without which universal access to drinking water, sanitation, and hygiene is not possible. It comprises of conducting gender-sensitive strategic planning workshops and strategic spatial analysis using Geographic Information Systems. It was implemented to Quezon City (QC), Philippines as pilot. The output is an action plan defining 15 Programs, Projects and Activities (PPAs) as solutions for water challenges across five development sectors (Social, Economic, Environmental, Land Use/Infrastructure, and Institutional) in the Philippines context. The appropriate implementation of these PPAs will ensure QC?s sustainable development, CC-resiliency, and its contribution to the country?s economic growth. The framework used is flexible and can be fashioned for the other cities in Global South countries and other regions. Keywords: Sustainable Development, Climate Change, Inclusive, Economic, Action Plan